# SOLUTION: If m^2 = 17 then what is the value of (m - 1)(m + 1) ? (A) &#8730;17 - 1 (B) &#8730;17 + 1 (C) 16 (D) 18 (E) 288

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: If m^2 = 17 then what is the value of (m - 1)(m + 1) ? (A) &#8730;17 - 1 (B) &#8730;17 + 1 (C) 16 (D) 18 (E) 288      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Polynomials-and-rational-expressions Question 252885: If m^2 = 17 then what is the value of (m - 1)(m + 1) ? (A) √17 - 1 (B) √17 + 1 (C) 16 (D) 18 (E) 288Answer by Theo(3458)   (Show Source): You can put this solution on YOUR website!m^2 = 17 means that m = +/- sqrt(17) (m-1)*(m+1) becomes: (sqrt(17)-1)*(sqrt(17)+1 or: (-sqrt(17) - 1) * (-sqrt(17) + 1) if (sqrt(17)-1)*(sqrt(17)+1, then the product of these 2 factors is processed as follows: sqrt(17) * sqrt(17) = 17 sqrt(17) * 1 = sqrt(17) -1 * sqrt(17) = -sqrt(17) -1 * 1 = -1 add these together to get 17 + sqrt(17) - sqrt(17) - 1 = 17 - 1 = 16 if (-sqrt(17)-1)*(-sqrt(17)+1, then the product of these 2 factors is processed as follows: -sqrt(17) * -sqrt(17) = 17 -sqrt(17) * 1 = -sqrt(17) -1 * -sqrt(17) = sqrt(17) -1 * 1 = -1 add these together to get 17 - sqrt(17) + sqrt(17) - 1 = 17 - 1 = 16 answer would be selection C (16).